Crossing (Intellectual) Frontiers, for the Love of Truth: Editorial Notes - Acetoso, Mattia; Tang, Wan Sonya (Romance eReview, 2019)
The yearly graduate conference, organized by the Department of Romance Languages and Literatures at Boston College, has become a pivotal moment in the intellectual life of our Master’s program. Every year, our graduate students take time off from their busy schedules to organize this event: they gather after class and brainstorm ideas for a central theme, discuss possible keynote speakers, plan every single aspect of the conference’s logistics. It is a labor of love and passion, one ultimately motivated by the desire to create a dialogue within our own program, and by the wish to cross the borders of disciplines and national traditions. Every spring, as a result of this effort, students from all over the country gather in Stokes Hall and offer their contribution to an intellectual conversation that would not have been possible otherwise. Romance eReview, both in its present incarnation and its previous printed form, has always sought to capture the liveliness of this conversation, immortalizing some of the best essays presented. The current issue of the journal includes a selection of works from two of the most recent conferences, “For the Love of Truth” (spring 2017) and “Crossing Fronteras/Frontières/Frontiere” (spring 2018), with the hope to offer visibility to these young authors and to celebrate their participation in our event.